Analisi Pola Spasial Hujan Ekstrim Metode Rerata Aljabar di Wilayah Lereng Barat dan Selatan Gunung Merapi - , MUH THAHA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mount Merapi is one of the active volcanos in Indonesia. This mount is located in Yogyakarta Special Province and Central Java Province. The Mount Merapi eruption can threat the thousands of people who live at around area of summit and the slope. The disaster risk happen when the eruption is happened, but also there is lahar flood can be secondary disaster. Therefore, it is necessary to conduct a study to minimize the damage risk due to of this lahar flood. The study of extreme rainfall pattern that is happened at slope of Mount Merapi can be used to be information of lahar flood early warning system. The main material of this research is analyzing the extreme rainfall pattern by algebra averaging method at West and South slope of Mount Merapi. The analysis of extreme rainfall pattern spatially uses the rainfall data that was measured by automatic rainfall recorder. The analysis was done to select rainfall event with heterogeneous specific duration (unisolated event) for duration of 1, 2, 3 and 4 hours since years 1981-2007. Furthermore, interpolation was done to draw the rainfall spatial maps by Inverse Distance Method (IDW) using ArcGIS software. The results show the spatial pattern of extreme rainfall that is expressed in rainfall intensity variety to the duration. The most frequent extreme rainfall intensity happens in a specific area, at West and South West of Mount Merapi. The extreme rainfall events are found in rainfall recorder station of Ngandong, Ngepos, Girikerto, Gunung Maron and Argomulyo area. Moreover, the extreme rainfall events happen in month January, February, November and December.